Myc and Ras oncogenes engage different energy metabolism programs and evoke distinct patterns of oxidative and DNA replication stress - Maya-Mendoza, Apolinar; Ostrakova, Jitka; Kosar, Martin; Hall, Arnaldur; Duskova, Pavlina; Mistrik, Martin; Merchut-Maya, Joanna Maria; Hodny, Zdenek; Bartkova, Jirina; Christensen, Claus; Bartek, Jiri (Molecular oncology, 2015)
Both Myc and Ras oncogenes impact cellular metabolism, deregulate redox homeostasis and trigger DNA replication stress (RS) that compromises genomic integrity. However, how are such oncogene-induced effects evoked and temporally related, to what extent are these kinetic parameters shared by Myc and Ras, and how are these cellular changes linked with oncogene-induced cellular senescence in different cell context(s) remain poorly understood. Here, we addressed the above-mentioned open questions by multifaceted comparative analyses of human cellular models with inducible expression of c-Myc and H-RasV12 (Ras), two commonly deregulated oncoproteins operating in a functionally connected signaling network. Our study of DNA replication parameters using the DNA fiber approach and time-course assessment of perturbations in glycolytic flux, oxygen consumption and production of reactive oxygen species (ROS) revealed the following results. First, overabundance of nuclear Myc triggered RS promptly, already after one day of Myc induction, causing slow replication fork progression and fork asymmetry, even before any metabolic changes occurred. In contrast, Ras overexpression initially induced a burst of cell proliferation and increased the speed of replication fork progression. However, after several days of induction Ras caused bioenergetic metabolic changes that correlated with slower DNA replication fork progression and the ensuing cell cycle arrest, gradually leading to senescence. Second, the observed oncogene-induced RS and metabolic alterations were cell-type/context dependent, as shown by comparative analyses of normal human BJ fibroblasts versus U2-OS sarcoma cells. Third, the energy metabolic reprogramming triggered by Ras was more robust compared to impact of Myc. Fourth, the detected oncogene-induced oxidative stress was due to ROS (superoxide) of non-mitochondrial origin and mitochondrial OXPHOS was reduced (Crabtree effect). Overall, our study provides novel insights into oncogene-evoked metabolic reprogramming, replication and oxidative stress, with implications for mechanisms of tumorigenesis and potential targeting of oncogene addiction.
Keywords: energetický metabolismus; protoonkogenní proteiny c-myc; oxidační stres; poškození DNA; Mitochondria; DNA Damage; Cell Line, Tumor; Ras; Cell Proliferation; Replication stress; Myc; Cell Death; buněčná smrt; Stress, Physiological; Genes, ras; geny ras; lidé; Energy Metabolism; Humans; DNA fork progression; replikace DNA; Proto-Oncogene Proteins c-myc; proliferace buněk; DNA Replication; nádorové buněčné linie; Oxidative Stress; fyziologický stres; Energy metabolism; DNA damage response; mitochondrie